STROKE DISEASE (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a scientific and critical analysis of stroke, its pathogenesis, clinical symptoms and treatment methods. Stroke can be a disease associated with a simple blood clot, but it can pose a significant threat to human health in older people. The article covers these aspects in detail and analyzes them based on various medical literature. It also focuses on preventive measures. The Ministry of Health is developing measures to prevent these and similar diseases and is using modern methods.